PEMELIHARAAN FASILITAS WATER TAP (Studi Kasus pada ITB dan UNS) - Bintoro, Gustauli (JPSI (Journal of Public Sector Innovations), 2018)
Maintenance of facilities or logistics is one of the functions of logistics management in the form of a series of activities or processes in which in the form of all forms of care, maintenance and care of the state of the goods for goods owned by an organization to remain usable at any time and able to achieve the economic age of the goods. This paper will discuss how the treatment of ready-to-drink water faucet facilities held by the Institute of Technology Bandung and Sebelas Maret University. This paper uses a qualitative descriptive study. to explain the maintenance of ready-to-drink water faucet facilities including the presence of inhibiting factors in their implementation. The results were found that in addition to problems in the processing unit, there are also problems in the piping network. This is an obstacle in the maintenance of water tap facilities. In addition, the participation of facility users is also important because if the water tap is not used then the water circulation will become not lanjar and the water that is accommodated on the pipe and the tank will be reflected bacteria that will continue to multiply and the water will only be disposed of into waste. Therefore both the facility manager and the facility user must maintain and care for the fasilita tap water ready to drink this properly.